Succeed and grow rich through persuasion : the greatest guide to wealth & happiness ever written - Hill, Napoleon (New Delhil : A & A Publishers)
Succeed And Grow Rich Through Persuasion is a guide to achieve success through the art of persuasion offers winning advice on how to increase self-confidence, cultivate a taste for success, and much more. This book is written in a manner that compelled you to take action. Succeed and Grow Rich Through Persuasion is a must read for everyone, but especially salespeople. Teachers, parents, husbands and wives will find this book makes them more persuasive in all of their dealings.